Stable expression of Mycobacterium bovis antigen 85B in auxotrophic M. bovis bacillus Calmette-Guérin - Rizzi, Caroline (Mem Inst Oswaldo Cruz, 2017)
BACKGROUND: Bovine tuberculosis (TB) is a zoonotic disease caused by Mycobacterium bovis, responsible for causing major losses in livestock. A cost effective alternative to control the disease could be herd vaccination. The bacillus Calmette-Guérin (BCG) vaccine has a limited efficacy against bovine TB, but can improved by over-expression of protective antigens. The M. bovis antigen 85B demonstrates ability to induce protective immune response against bovine TB in animal models. However, current systems for the construction of recombinant BCG expressing multiple copies of the gene result in strains of low genetic stability that rapidly lose the plasmid in vivo. Employing antibiotic resistance as selective markers, these systems also compromise vaccine safety. We previously reported the construction of a stable BCG expression system using auxotrophic complementation as a selectable marker. OBJECTIVES: The fundamental aim of this study was to construct strains of M. bovis BCG Pasteur and the auxotrophic M. bovis BCG ΔleuD expressing Ag85B and determine their stability in vivo. METHODS: Employing the auxotrophic system, we constructed rBCG strains that expressed M. bovis Ag85B and compared their stability with a conventional BCG strain in mice. Stability was measured in terms of bacterial growth on the selective medium and retention of antigen expression. FINDINGS: The auxotrophic complementation system was highly stable after 18 weeks, even during in vivo growth, as the selective pressure and expression of antigen were maintained comparing to the conventional vector. MAIN CONCLUSION: The Ag85B continuous expression within the host may generate a stronger and long-lasting immune response compared to conventional systems.